2021
DOI: 10.1002/cre2.451
|View full text |Cite
|
Sign up to set email alerts
|

CBCT‐based assessment of the anatomic relationship between maxillary sinus and upper teeth

Abstract: Objectives: To describe the relationship between maxillary sinus (MS) and upper teeth based on cone beam computed tomographic scans (CBCT). Materials and methods:Based on CBCT maxillary imaging data of 147 patients, distance between MS and apices of canines and posterior maxillary teeth were assessed.Distances between tooth roots and sinus were classified into three groups: distant (>2 mm), close (<2 mm) or in contact with MS. Teeth with apical lesions and uncommon root configurations were excluded.Results: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
5
0
2
Order By: Relevance
“…However, in this study, the FMS-P distance was less than 0.5 mm in both the first and second molars, and the palatal intruded into the sinus in 49% and 30% of the first and second molars, respectively. Other studies have reported similar findings, with palatal root intrusion into the sinus ranging between 29% and 73% and 23% and 69% for first and second molars, respectively [13,18].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, in this study, the FMS-P distance was less than 0.5 mm in both the first and second molars, and the palatal intruded into the sinus in 49% and 30% of the first and second molars, respectively. Other studies have reported similar findings, with palatal root intrusion into the sinus ranging between 29% and 73% and 23% and 69% for first and second molars, respectively [13,18].…”
Section: Discussionsupporting
confidence: 70%
“…The close relationship between molar roots and the sinus floor has been emphasized in several studies [ 9 , 13 , 16 , 17 ]. Some studies have reported that the MB and DB roots of the second molar are those that are most often in contact with the sinus floor [ 10 , 18 ], while others have indicated that the palatal root commonly intrudes into the sinus [ 19 , 20 ]. The differences in these findings could be attributed to differences in the evaluation techniques and study populations and may suggest a racial/ethnic disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, Sharan & Madjar (2006) y Ali et al (2012) reportaron que la posición más frecuente era que el ápice se encontraba en contacto con el seno maxilar, lo que se puede atribuir a que ambos utilizaron una categoría más en su clasificación para evaluar la relación entre ambas estructuras (el ápice está envuelto por un piso del seno con curvatura superior). Al analizar cada raíz del 1M, se observó que la raíz P fue la que presentó mayor frecuencia de protrusión en el seno maxilar (42 %) lo que concuerda con la literatura (Kang et al, 2015;Regnstrand et al, 2021). Sin embargo, Jung & Cho (2012) reportaron que la raíz MV se encontraba con mayor frecuencia protruida, lo que se podría deber a que el análisis de las imágenes se realizó en el plano coronal y no en el plano sagital.…”
Section: Discussionunclassified
“…El conocimiento de la relación de los dientes posterosuperior con el seno maxilar es de gran importancia para el odontólogo, ya que le permite analizar distintas alternativas de tratamiento, pronósticos, y prever posibles complicaciones cuando se realicen actos quirúrgicos relacionadas con dicha zona (Regnstrand et al, 2021). Para esto, el cirujano debe apoyarse en exámenes complementarios dentro de los cuales destaca la tomografía computarizada de haz cónico (TCHC).…”
Section: Introductionunclassified
“…Most of the previous studies assessing the relationship between upper teeth and MS have utilized two‐dimensional (2D) imaging. However, 2D imaging offers limited information as it compresses the 3D structures, leading to misinterpretation of the relation between upper teeth and MS with a potential risk for misdiagnosis of pathology associated with the posterior maxilla (Estrela et al, 2016 ; Kilic et al, 2010 ; Nino‐Barrera et al, 2018 ; Regnstrand et al, 2021 ; Shahbazian et al, 2014 , 2015 ; von Arx et al, 2014 ). Three‐dimensional imaging using cone‐beam computed tomography (CBCT) may offer a solution to better visualize the complex representation of MS in relation to upper (pre)molars.…”
Section: Introductionmentioning
confidence: 99%